Penggunaan Kecerdasan Buatan untuk Pembelajaran Bahasa Arab yang Adaptif dan Terpersonalisasi - Rohim, Aulya Fathur; Maslamah, Maslamah; Qosim, Muh. Nanang (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
Artificial intelligence is a breakthrough and advancement that focuses on the needs and demands of students. Over time, digital transformation has undergone rapid development. This has a significant impact on the growth of various sectors, including the education sector. Technology or Artificial Intelligence (AI) has experienced significant developments along with technological advances. The presence of AI is increasingly affecting all aspects of human life, especially in the field of education. Therefore, in the realm of education, utilizing technology in schools or universities is a wise move, as it not only facilitates access to information but also helps in independent learning. The use of AI in Arabic language learning can be used in translation, Arabic grammatical learning and can also be used in helping muhadatsah activities. The aim of this study is to elucidate the role of AI in building adaptive and personalized learning ecosystems, particularly in Arabic language education. The method used in this study is a literature review or literature research with a qualitative approach, data data collected from various literature in the form of scientific journals, books, and several other scientific discoverie